Self-Validation of Cognitive Responses to Advertisements - Briñol, Pablo; Petty, Richard E.; Tormala, Zakary L. (Journal of Consumer Research, 2004)
Two studies tested the notion that the confidence consumers have in their cognitive responses to an ad can increase or decrease the favorability of product attitudes. Increasing confidence in positive thoughts enhanced advertisement effectiveness. Increasing confidence in negative thoughts reduced advertisement effectiveness. These self-validation effects occurred regardless of the type of product and regardless of whether thought confidence was measured or induced through an experimental manipulation. The present research also demonstrated that source credibility can influence consumer attitudes by affecting thought confidence. Finally, thought confidence was distinguished from other potentially related thought dimensions. Antecedents, moderators, and consequences of self-validation effects are described.